2017
DOI: 10.1093/biolre/iox074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cysteine-X-cysteine motif chemokine ligands 9, 10, and 11, their receptor CXCR3, and their possible role on the recruitment of immune cells at the maternal–conceptus interface in pigs†

Abstract: Chemokines play critical roles in the establishment and maintenance of pregnancy in animals. Cysteine-X-cysteine motif chemokine ligand 9 (CXCL9), CXCL10, and CXCL11 are involved in recruiting immune cells by binding to their shared receptor, CXC receptor 3 (CXCR3), in a variety of tissues. This study examined the expression and regulation of chemokines CXCL9, CXCL10, and CXCL11, their receptor CXCR3, and their role at the maternal-conceptus interface in pigs. The endometrium expressed CXCL9, CXCL10, CXCL11, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Th1 cytokines activate cell-mediated immunity that is deleterious for pregnancy, while Th2 cytokines are involved in humoral immunity that is beneficial for fetal survival and leads to maternal immune tolerance to the developing fetus [ 52 ]. In the porcine endometrium, there are many immune cells recruited into the endometrium during early pregnancy [ 53 ] and recruitment of T cells and NK cells into the endometrium is greatest on Day 15 of pregnancy [ 54 ], when the conceptus attachment to the endometrial epithelial cells occurs. Our results indicate that IL10 production increases and IL12 production decreases in the endometrium during early pregnancy (Han and Ka, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cytokines activate cell-mediated immunity that is deleterious for pregnancy, while Th2 cytokines are involved in humoral immunity that is beneficial for fetal survival and leads to maternal immune tolerance to the developing fetus [ 52 ]. In the porcine endometrium, there are many immune cells recruited into the endometrium during early pregnancy [ 53 ] and recruitment of T cells and NK cells into the endometrium is greatest on Day 15 of pregnancy [ 54 ], when the conceptus attachment to the endometrial epithelial cells occurs. Our results indicate that IL10 production increases and IL12 production decreases in the endometrium during early pregnancy (Han and Ka, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike IFN-τ (IFNT), a type I IFN produced by the conceptus and acting as a signal for maternal recognition of pregnancy by preventing endometrial production of luteolytic PGF 2α in ruminants [ 17 ], IFND and IFNG do not have an anti-luteolytic effect in pigs [ 18 ]. IFNs secreted by the conceptus trophectoderm induce many IFN-stimulated genes and class I and II major histocompatibility complex (MHC) molecules in the endometrium [ 19 22 ], but detailed function of IFNs at the maternal-conceptus interface is not fully understood in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Works of Joyce et al (Joyce et al, ; Joyce, Burghardt, Burghardt et al, ; Joyce, Burghardt, Geisert et al, ) indicate that conceptus secretory proteins from the conceptus‐conditioned culture medium increase endometrial expression of STAT1, STAT2, IRF1, SLA1,2,3,6,7,8 , and B2M (β2 microglobulin), suggesting that IFNG and/or IFND stimulate expression of these genes in the endometrium. Our recent studies on pigs have shown that IFNG induces the endometrial expression of SLA‐DQA and SLA‐DQB (Kim et al, ), TLR7 (Yoo et al, ), and chemokines cysteine‐X‐cysteine motif chemokine ligand 9 (CXCL9), CXCL10, CXCL11, and CXCL12 (Han et al, ). These molecules are involved in endometrial immune responses and CXCL9, CXCL10, CXCL11, and CXCL12 have been indicated to regulate the recruitment of immune cells into the endometrium at the time of conceptus implantation.…”
Section: Discussionmentioning
confidence: 99%